Warnings unheeded : twin tragedies at Fairchild Air Force Base - Brown, Andrew P. (WU Press, 2016)
"A revealing look at the events that led to a mass murder and a fatal plane crash at Fairchild Air Force base. Those who recognized a mentally ill airman's potential for violence and tried to help him were frustrated by politics and buraucracy. When the troubled airman opened fire in Fairchild's hospital, an Air Force security policeman was prepared for the gunfight and hospital personnel were prepared to save lives. But no one was prepared for the traumatic aftermath. A B-52 pilot was a crowd favorite at Fairchild's air shows but his reckless maneuvers caused some airmen to refuse to fly with him. He was protected from disciplinary action and attempts to ground him, but nothing could save him when he pushed too far during an airshow practice mission four days after the shooting."-- back cover